Cyprus : Financial Sector Assessment Program Update; Technical Note; Factual Update of IOSCO Core Principles of Securities Regulation. (IMF Staff Country Reports; Country Report, 2009)
This technical note presents factual update of International Organization of Securities Commissions Core Principles of Securities Regulation for Cyprus. There is provision in the law allowing for the sharing of information and cooperation with both domestic and foreign regulators. The Cyprus law transposing the European Union Prospectus and Transparency Directives, together with the company law and stock exchange law, provide accurate and timely disclosure of financial results and adequate safeguards in the fair and equitable treatment of shareholders.